Nathaniel Pope, Laws of the Territory of Illinois 25 (1815) - (:unkn) unknown (My University, 1810)
An Act to suppress duelling, Adopted from the Virginia Code: Prohibited fighting or agreeing to fight in a duel with any engine instrument or weapon where the probably consequences might be death of either party, and in doing so shall kill his antagonist or any other person, or inflict such a wound that the person injured shall die thereof within three months. Any violators, their aiders, abettors, and councillors thereof duly convicted shall be guilty of murder and suffer death by hanging.
Keywords: DUELING